2'3'-Dideoxycytidine-induced thymic lymphoma correlates with species-specific suppression of a subpopulation of primitive hematopoietic progenitor cells in mouse but not rat or human bone marrow. - Irons, R D; Le, A T; Som, D B; Stillman, W S (The Journal of Clinical Investigation, 1995)
The nucleoside analogue, 2',3'-dideoxycytidine (ddC), is a potent inhibitor of HIV replication, and AIDS patients receiving ddC experience clinical improvement without significant hematologic toxicity. Repeated ddC administration (1,000 mg/kg per day) for 13 wk produces an increased incidence of thymic lymphoma in B6C3F1 mice. Previous studies reveal a common link between chemically induced and genetically associated models of mouse thymic lymphoma that involves a defect in a subpopulation of primitive hematopoietic progenitor cells. This defect is characterized by suppression of a subpopulation of IL-3-responsive cells and ablation of stem cell factor synergy with GM-CSF. The present study was undertaken to ascertain whether ddC produces the same pattern of bone marrow toxicity in mice, and whether this effect is observed in rat and human bone marrow. ddC exposure in vivo and in vitro produced a select suppression of murine CFU identical to that previously described for other models of mouse thymic lymphoma. In contrast, this selective CFU suppression was not observed in rat and human bone marrow or in CD34+ cells. These studies suggest that the mouse may not be a good predictive model for ddC hematotoxicity in humans and that susceptibility to the development of thymic lymphoma may be unique to the mouse. Images